Feasibility and acceptability of Indigenous Counselling and Nicotine (ICAN) QUIT in Pregnancy multicomponent implementation intervention and study design for Australian Indigenous pregnant women: A pilot cluster randomised step-wedge trial. (March 2019) - Gould, Gillian S.; Bovill, Michelle; Pollock, Lauren; Bonevski, Billie; Gruppetta, Maree; Atkins, Lou; Carson-Chahhoud, Kristin; Boydell, Katherine M.; Gribbin, Gabrielle R.; Oldmeadow, Chris; Hall, Alix; Bar-Zeev, Yael; et al.
Abstract: Background: Many health providers (HPs) lack knowledge, confidence, optimism and skills in addressing smoking with pregnant women. This study aimed to explore the feasibility and acceptability of a) a co-designed multi-component intervention for HPs at Aboriginal Medical Services (AMSs) in culturally-targeted pregnancy-specific smoking cessation care and b) the study design. Methods: Using a randomised step-wedge cluster design, the Indigenous Counselling And Nicotine (ICAN) QUIT in Pregnancy Trial was evaluated across six AMSs in three Australian states. HPs were provided educational resource packages including live interactive webinars, treatment manuals, patient resources, carbon monoxide (CO) meters, and oral Nicotine Replacement Therapy (NRT). Feasibility was assessed through recruitment and retention rates of both pregnant women (12-weeks) and HPs (end of study) as well as the potential to improve women's quit rates. Qualitative interviews with staff post-trial explored acceptability of the intervention and study, based on capability, opportunity and motivation from the Behaviour Change Wheel. Results: Pregnant women (n = 22; 47% (95% CI: 32%, 63%) eligible) and HPs (n = 50; 54% (95% CI: 44%, 64%) eligible) were recruited over 6 months with retention rates of 77% (95% CI: 57%, 90%) and 40% (95% CI: 28%, 54%) respectively. Self-reported 12-week 7-day point-prevalence abstinence was 13.6% (n = 3) and validated abstinent with CO readings ≤6 ppm. Staff interviewed regarding intervention implementation highlighted the importance of provision and use of resources, including training materials, patient resources, CO meters and oral NRT. Resources helped increase capability and opportunity, restructure the environment, and provided social comparison and modelling. Staff were motivated by greater engagement with pregnant women and seeing the women's reductions in CO readings. Having the intervention at the AMSs improved organisational capacity to engage with pregnant women. Staff reported changes to their routine practice that were potentially sustainable. Recommendations for improvement to the implementation of the intervention and research included reducing training length and the tasks related to conducting the study. Conclusion: ICAN QUIT in Pregnancy was a pilot study with the ability to enrol Indigenous women. It was feasible to implement and acceptable to most staff of the AMSs in three states, with modifications recommended. Smoking in pregnancy is a key challenge for Indigenous health. The intervention needs to be evaluated through a methodologically rigorous fully-powered study to determine the efficacy of outcomes for women. Trial registration: Australian and New Zealand Clinical Trials Registry, ACTRN12616001603404. Registered 21 November 2016 - retrospectively registered, https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=371778 Highlights: Resources targeted to Indigenous smoking cessation in pregnancy were well-received. Health staff were motivated by engagement with Indigenous pregnant women. Many Indigenous women made quit attempts, and 13.8% quit smoking. ICAN QUIT in Pregnancy was feasible and acceptable to Aboriginal Medical Services. Modifications were recommended by health staff to trial design and survey length.